Gradient system processed data from the expedition ARTofMELT, Arctic Ocean, 2023 - Theresa Mathes; Andreas Held (PANGAEA, 2025)
In spring 2023, near-surface particle and heat fluxes were measured using the gradient method during the ARTofMELT Arctic Ocean Expedition aboard the icebreaker Oden. The gradient system was used to measure the number of particles, temperature and wind speed at five different heights close to the surface. We divided the surface conditions into three categories: open water, open lead and closed ice. To measure the concentration of particles near the surface, we used a 1.50 m high linear actuator with a sensor board. The sensor board included a temperature sensor, a heat wire anemometer, an inlet connected to a condensation particle counter (CPC) and a distance sensor. The gradient system was set up to approach six different height levels in sequence. The distance to the surface from the inlet varied depending on the height level, with measurements taken at 5 cm, 10 cm, 17 cm, 32 cm, 67 cm and 129 cm.
In: Mathes, T; Held, A (2025): Particle flux-gradient relationships for the expedition ARTofMELT, Arctic Ocean, 2023 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974992